A Comparative Study of Proximal Femoral Nail and Dynamic Hip Screw in the Treatment of Intertrochanteric Fractures of Femur - Muhammad Sarfraz, Saeed Ahmad, Muhammad Shahbaz Raza, Syed Alam Zeb, Sartaj Lakhani, Rahim Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this analysis is the comparison of the functional and radiological results of stable intertrochanteric femoral fractures managed with the dynamic hip screw (DHS) and proximal femoral nail (PFN). Study Design: A Randomized, controlled study. Place and Duration: In the Orthopaedics department of Capital Hospital (CDA), Islamabad for two years duration from January 2020 to December 2021. Methods: All patients with stable intertrochanteric fractures who met the criteria of selection were randomly allocated to group A (DHS) and B (PFN). There were 80 total patients alienated into group A and B. Patients were x-rayed for union evaluation and functional evaluation was done with Harris Hip Score (HHS) was performed, rated as poor (score <70), good (80 to 90), fair (70 to 80) and excellent (90 to 100). The comparison of the results in the two groups was made at the third, sixth and twelfth months, and the P value was calculated using the chi-square test and the independent sample t-test. P <0.05 was measured significant. Results: There were 80 total patients. They were divided equally and randomly into groups A and B of 40 patients each. The PFN group had a shorter operative time, smaller incision and minimum blood loss intraoperatively than the DHS group (p <0.05). The group A mean age was 60.10±4.48 years, and of group B was 59.20±5.71 years. There were 25 men (62.5%) in A group and 23 (57.5%) in B group. Women were 15 (37.5%) in A group and 17 (42.5%) in B group. Mean time of radiological union was 14.2±4 weeks in group A and 12.8±6 weeks in group B (P> 0.05). During the 3-month follow-up period, the Harris Hip Score (HHS) was 54.20 ± 4.20 (poor) and 35.03 ± 4.11 (poor) in Groups A and B, correspondingly (P <0.05). HHS in group A was 90.27 ± 3.80 (good) and in B group, it was 82.27 ± 3.65 (good) (P <0.05) at 6 months and HHS 94.61 ± 2.08 (excellent) and 93.27 ± 2.18 (excellent) 1 year in the group A and B (P> 0.05). Conclusions: Both DHS and PFN gave similar results in terms of radiological union in stable intertrochanteric fractures. The short-term functional score was poor and good for both DHS and PFN at 3 and 6 months, although DHS scored statistically better than PFN. After one year of follow-up, both DHS and PFN had similar excellent functional scores, but had no statistically significant difference in score.